Understanding the Barriers and Challenges Between Older Users and Smartphones: A Systematic Literature Review - Paschoarelli, Luis Carlos [UNESP]; Fernandes, Nathan Martins [UNESP]; Ferro-Marques, Larissa R. [UNESP] (Springer Nature, 2021)
Older adults are a significant part of the world population and new Information Technologies (ITs) will have an essential role in maintaining the quality of life and social integration of this population. However, the interfaces of different Its—especially smartphones—do not yet satisfy the characteristics, needs and expectations of older adults since they present physical, cognitive and emotional barriers that disappoint these users. The present study was based on a Systematic Literature Review (SLR), and aimed to analyze the main barriers experienced by older adults when using smartphones. Three aspects were highlighted for the present analysis: the physical, cognitive and emotional. The SLR has shown that much progress has been made to understand the interaction problems between older users and smartphones. However, many barriers remain, creating difficulties of use and limiting the effective contribution of IT to these users. Thus, guidelines based on physical, cognitive and emotional aspects, essential for the new ergonomic design of smartphones, are compiled and presented.
Keywords: Emotion; Older users; Smartphone